Mouse models as a tool to study asymptomatic DENV infections - Henriques, Paulo; Rosa, Alexandra; Caldeira-Araújo, Helena; Vigário, Ana Margarida (Frontiers in Cellular and Infection Microbiology, 2025)
Asymptomatic outcome accounts for most dengue virus infections and is likely to play an important role in maintaining virus circulation, contributing to its dissemination and shortening inter-epidemic periods. While dengue immunopathogenesis, investigation of potential therapeutics, and vaccine efficacy have been widely studied, only recently have inapparent infections begun to be comprehensively addressed as an integral and important part of the puzzle that is dengue infection. Animal models are one of the tools utilized to study dengue and, among these, mouse models have played an important role in understanding both dengue pathogenesis and the hosts’ initial immune response. However, these models have mostly focused on untangling the drivers of disease severity ignoring asymptomatic dengue virus infections. In this mini-review, the authors propose to provide a concise overview of the current state-of-the-art of existing mouse models with potential use for studying asymptomatic dengue virus infections, elaborating on the pros and cons of the several models. Variations in experimental conditions, such as altering the viral load of the inoculum or employing different virus entry routes, especially in mice with partial or transient blockade of the type I interferon response, might be sufficient to obtain both symptomatic and asymptomatic viremic mice. This would enable the study of factors involved in asymptomatic dengue virus infections.